2017
DOI: 10.1302/0301-620x.99b10.bjj-2017-0034.r1
|View full text |Cite
|
Sign up to set email alerts
|

Revision total knee arthroplasty for failed high tibial osteotomy and unicompartmental knee arthroplasty have similar patient-reported outcome measures in a two-year follow-up study

Abstract: Revision of HTO and UKA achieve similar post-operative PROMs and satisfaction. Revision of UKA more frequently requires revision components with increased operation duration but fewer complications requiring re-operation compared with revision of HTO. Cite this article: 2017;99-B:1329-34.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…However, a direct comparison of the survival estimates from these studies is prone to confounding by indication due to a range of unadjusted baseline characteristics associated with the survival of TKA, such as implant constraints and hospital volume of arthroplasty surgeries (Jasper et al 2016). This concern is further encouraged by a recent single-center study reporting similar short-term survival of TKA following UKA and TKA following HTO (Lim et al 2017). Based on the Danish Knee Arthroplasty Registry (DKR), our study compares the survival of TKA converted from UKA with TKA converted from HTO with consideration for confounding by indication utilizing propensity-score based inverse probability of treatment weighting (PS-IPTW) (Inacio et al 2015).…”
mentioning
confidence: 99%
“…However, a direct comparison of the survival estimates from these studies is prone to confounding by indication due to a range of unadjusted baseline characteristics associated with the survival of TKA, such as implant constraints and hospital volume of arthroplasty surgeries (Jasper et al 2016). This concern is further encouraged by a recent single-center study reporting similar short-term survival of TKA following UKA and TKA following HTO (Lim et al 2017). Based on the Danish Knee Arthroplasty Registry (DKR), our study compares the survival of TKA converted from UKA with TKA converted from HTO with consideration for confounding by indication utilizing propensity-score based inverse probability of treatment weighting (PS-IPTW) (Inacio et al 2015).…”
mentioning
confidence: 99%
“…Comparing both conversions following UKA and HTO with primary TKA, both revisions are technically more demanding and require more resources. 22,37,[41][42][43] In our study, conversion TKA following UKA required more revision components and thicker polyethylene. They might be necessary to fill the bone defects at sites where UKA components have been removed.…”
Section: Discussionmentioning
confidence: 48%
“…Moreover, it may confront the difficulty of surgical approach, imbalance of the collateral ligaments, and anatomical distortion of the proximal tibial metaphysis. 22,41,42 As the number of UKA and HTO increases, revisions after UKA and HTO are also increasing. As the results of our study, conversion TKA following UKA and HTO requires more revision components than the primary TKA, which inevitably leads to an increase in the cost of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There were no statistically 20 However, many studies have demonstrated that HTO and DFO can be used without impacting revision TKA outcomes. [21][22][23][24][25] Despite this, longitudinal trends suggest a decline in the use of HTO and DFO in the United States and in favor of unicompartmental or TKA. 19,[26][27][28] This is in contrast to countries such as Japan 29 and Korea 30 that demonstrated increased usage of HTO and DFO for knee OA.…”
Section: Resultsmentioning
confidence: 99%